Factores asociados a la resistencia psicológica a la insulina en pacientes diabéticos de un hospital público de Loreto, 2023 - Vásquez Llerena, Elías Moisés (2024)
Objectives: To determine the factors associated with psychological insulin resistance in diabetic patients at the Regional Hospital of Loreto during October and November 2023. Methods: A quantitative, descriptive, and cross-sectional study was conducted. Results: A prevalence of 77.78% of negative perception of insulin was found, translating into psychological insulin resistance in the studied population, with 70,5% of these cases being female. A statistically significant association was found between clinical and sociodemographic characteristics. Specifically, an association was observed between diabetes duration of less than 10 years (p=0.032), the use of at least one oral antidiabetic (p=0.001), not insulin use (p=0.000), educational level (p=0.026), and psychological insulin resistance. Conclusions: Crucial factors associated with psychological insulin resistance were identified in diabetic patients at the Regional Hospital of Loreto, shedding light on the complex interactions of clinical and sociodemographic variables contributing to psychological insulin resistance. This provides a comprehensive understanding of psychological determinants in the management of diabetes and insulin therapy.